1989
DOI: 10.1002/ardp.19893220508
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrylalkanoic Acids, III: Syntheses and Biological Activities of 4‐Phenanthryl Derivatives

Abstract: Reformatsky reactions between 2,3-dihydro-4(1H)-phenanthrenone (5) and ethyl alpha-bromoacetate or propanoate yield several unsaturated esters which, upon aromatization followed by saponification, lead to the 4-phenanthrylacetic (1) and 2-(4-phenanthryl)propanoic (2) acids. The analgesic and anti-inflammatory properties of 1 and 2 were measured and compared with those of Fenbufen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Mechanistic studies showed that several drops of methanol were sufficient to accelerate the oxidative addition of carboN−chloride bonds by forming highly active but relative stable 14e species ( Pd 0 L(MeOH) ) no matter the ratio of ligands/Pd (1 : 1 or 1 : 2) was employed, and to boost the boronic acid ( 12 ) activation, thereby significantly increased the reaction efficiency. With the developed methodology, Fenbufen ethyl ester ( 15 a , anti‐inflammatory API), [50] Bifenthrin intermediate ( 15 b , insecticide) [51] and Fluxapyroxad ( 15 c , fungicide) [51a,52] can be easily attained from stable and economic chlorinated aromatics with excellent yields and minimal environmental impacts.…”
Section: Mechanochemical C−x Functionalization For Apis and Bioactive...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic studies showed that several drops of methanol were sufficient to accelerate the oxidative addition of carboN−chloride bonds by forming highly active but relative stable 14e species ( Pd 0 L(MeOH) ) no matter the ratio of ligands/Pd (1 : 1 or 1 : 2) was employed, and to boost the boronic acid ( 12 ) activation, thereby significantly increased the reaction efficiency. With the developed methodology, Fenbufen ethyl ester ( 15 a , anti‐inflammatory API), [50] Bifenthrin intermediate ( 15 b , insecticide) [51] and Fluxapyroxad ( 15 c , fungicide) [51a,52] can be easily attained from stable and economic chlorinated aromatics with excellent yields and minimal environmental impacts.…”
Section: Mechanochemical C−x Functionalization For Apis and Bioactive...mentioning
confidence: 99%
“…[13c] In their established Pd(OAc) 2 /PCy 3 •HBF 4 /K 2 CO 3 /MeOH system, unprotected p-chloroaniline gave solely CÀ C bond coupling product, and no trace of CÀ N bond formation (Buchwald-Hartwig crosscoupling side reaction) was detected, exhibited an excellent chemo-selectivity control. Mechanistic studies showed that several drops of methanol were sufficient to accelerate the oxidative addition of carboNÀ chloride bonds by forming highly active but relative stable 14e species (Pd 0 L(MeOH)) no matter the ratio of ligands/Pd (1 : 1 or 1 : 2) was employed, and to boost the boronic acid ( 12 Fenbufen ethyl ester (15 a, anti-inflammatory API), [50] Bifenthrin intermediate (15 b, insecticide) [51] and Fluxapyroxad (15 c, fungicide) [51a,52] can be easily attained from stable and economic chlorinated aromatics with excellent yields and minimal environmental impacts.…”
Section: Mechanochemical Suzuki-miyaura Cross-couplingmentioning
confidence: 99%